ITEM ANALYSIS OF AN GENERAL MANAGEMENT AWARENESS/ LEARNING ASSESSMENT TEST IN BUSINESS SCHOOL FOR ITS DIFFICULTY INDEX, DISCRIMINATION INDEX, AND DISTRACTOR ANALYSIS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Nowadays, Item analysis is an important tool  to know the functionality of the set items used  in a test, prepared to access the learning level  of student. An item which is a multiple-choice  question with more than one option out of one  is a correct answer called a key and the rest is  an incorrect answer(s) called a distractor(s).  The main objective of the distractor is to divert  the student from the correct answer. Good  distractor(s) is always a plausible answer. So to  understand the function of the distractor(s),  the distractor analysis is very important. In this  study, we analyzed the different statistics of item  analysis namely difficulty index, discrimination  index, distractors, etc. and understand how they  are functioning.
Keywords: Assessment test; item analysis; discrimination index; distractor analysis